Molecular phylogeography of a widespread Malagasy leaf chameleon species, Brookesia superciliaris - Ratsoavina, Fanomezana M.; Gehring, Philip-Sebastian; Ranaivoarisoa, Freddy J.; Rafeliarisoa, Tsilavo H.; Crottini, Angelica; Louis Jr., Edward E.; Vences, Miguel (Zootaxa, 2010)
Chameleons of the Madagascan endemic genus Brookesia Gray are small to extremely small reptiles with a mostly terrestrial lifestyle, and due to their low mobility and their camouflage they are nearly invisible in the leaf litter of Madagascar's forests. The genus Brookesia is widely distributed (except in the arid south and south-west) but many Brookesia species are restricted to a relatively small area of the island (Glaw & Vences 2007). Speciation has been most prolific in the northern parts of Madagascar, an area that currently host about two-thirds of the 27 nominal Brookesia species (Raxworthy & Nussbaum 1995; Glaw & Vences 2007; Townsend et al. 2009).